Left Atrium and Left Atrial Appendage Remodeling Assessed by Echocardiography Predict Atrial Fibrillation Recurrence After Radiofrequency Catheter Ablation - Binyang Zhu; Shaohui Qu; Hairu Li; Dandan Yu; Yingying Liu; Xin Ai; Guangyin Li; Shuangquan Jiang (Clinical Cardiology, 2026)
ABSTRACT Purpose The aim of this study is to evaluate left atrium (LA) and left atrial appendage (LAA) remodeling using two‐dimensional speckle tracking echocardiography (2D‐STE) and investigate its predictive value for atrial fibrillation (AF) recurrence after radiofrequency catheter ablation (RFCA). Methods One hundred patients with AF underwent TTE and TEE before undergoing RFCA. LA and LAA strain and strain rate values obtained by 2D‐STE. Logistic regression analysis was used to analyze independent contributors for AF recurrence after RFCA. The prediction efficiency of clinical ultrasound parameter models associated with the presence of AF recurrence was evaluated by the receiver operating characteristic (ROC) curve with area under curve (AUC). Results ①During the 1‐year follow‐up, 33% of patients experienced AF recurrence. ②The recurrent group had significantly higher NLR, NT‐proBNP, and LAVImin values compared to the non‐recurrent group ( p < 0.05). ③The recurrence group had significantly lower LAEF, LAEI, LAA‐EV, LAS, LASR, LAAS, LAASR values than the non‐recurrent group ( p < 0.05). ④LAAS and LAASR were potential factors contributing to AF recurrence ( p < 0.05). In addition, incorporating LAAS and LAASR into predictive models can provide extra valuable information to identify patients at a higher risk of AF recurrence. Conclusion LAAS and LAASR, as obtained by 2D‐STE, are potential predictors of AF recurrence after RFCA. By incorporating these 2D‐STE parameters into preoperative clinical data along with TTE and TEE, it may be possible to identify impaired LA/LAA function in AF patients early. This could aid in choosing suitable patients and improving the benefit ratio of RFCA.